Inclusive Education in Elementary Schools: Creating a Welcoming and Character Building Learning Environment - Aning Rosyidah (GENIUS: Journal of Elementary Pedagogy and Innovation Studies, 2026)
Inclusive education in elementary schools is an effort to build a friendly and character-building learning environment, particularly at SDN Sumberagung 2 Wates Jawa Timur. This research is motivated by the challenges of creating an inclusive and character-building learning atmosphere amidst student diversity. The aim of this study is to evaluate and develop effective inclusive learning strategies at SDN Sumberagung 2 Wates Jawa Timur. The research method used is qualitative with a literature study approach. Data were obtained through the review and analysis of various references such as books, scholarly journals, articles, and other documents related to the topic. The researcher then drew conclusions from the findings and reviews conducted. The implications of this study show that well-designed inclusive education can enhance active participation, creativity, and character development of students. Additionally, schools that implement inclusive principles are also able to create a more equitable and harmonious learning environment, reduce discrimination, and strengthen social relationships among students. This study provides recommendations for expanding teacher training programs and developing school policies that comprehensively support inclusion.